Three-dimensional printing of a complex CHD to plan surgical repair. (20th June 2016) - Hadeed, Khaled; Dulac, Yves; Acar, Philippe
Abstract: We used three-dimensional printing technology to create an anatomical three-dimensional model of a very rare and complex cyanotic CHD in a newborn, consisting of double-outlet left ventricle, ventricular septal defect, and pulmonary stenosis. This case demonstrates how this new innovative technology allows better understanding of the anatomy in complex CHDs and permits to better plan the surgical repair.